Effects of Small-Sided Game Interventions on the Technical Execution and Tactical Behaviors of Young and Youth Team Sports Players: A Systematic Review and Meta-Analysis - Clemente, Filipe Manuel; Ramirez-Campillo, Rodrigo; Sarmento, Hugo; Praça, Gibson Moreira; Afonso, José; Silva, Ana Filipa; Rosemann, Thomas; Knechtle, Beat (Frontiers in Psychology, 2021)
Background: Small-sided games (SSGs) are an adjusted form of official games that are often used in training scenarios to introduce a specific tactical issue to team sports players. Besides the acute effects of SSGs on players’ performance, it is expectable that the consistent use of these drill-based games induces adaptations in the technical execution and tactical behaviors of youth team sports players. Objective: This systematic review with meta-analysis was conducted to assess the effects of SSG programs on the technical execution and tactical behaviors of young and youth team sports players. Data sources: The data sources utilized were PubMed, Scopus, SPORTDiscus, and Web of Science. Study eligibility criteria: (i) Young and youth team sports players (i.e., < 18 years old) of any sex or skill level, without injury, illness, or other clinical conditions; (ii) SSGs-based programs not restricted to the duration and a minimum of one weekly training session; (iii) passive or active control groups; (iv) pre-post interventions values of technical execution and/or tactical behavior; (v) randomized and non-randomized controlled trials; and (vi) peer-reviewed original full-text studies written in English, Portuguese and/or Spanish. Results: The database search initially yielded 803 titles. From those, six articles were eligible for the systematic review and meta-analysis. None of the included studies presented tactical behavior outcomes. The results showed a small effect of SSGs on technical execution (ES = 0.59; 95% CI = 0.29 to 0.89; p < 0.001; I2 = 0.0%; Egger’s test p = 0.590) when compared to controls. Sub-group analysis of the training factor revealed similar (p = 0.433) moderate (ES = 0.68, four study groups) and small (ES = 0.44, three study groups) improvements in technical execution after >17 and <17 SSG training sessions, respectively. Conclusions: This systematic review and meta-analysis revealed a significant beneficial effect of using SSG training programs for enhancing technical execution in young and youth players. The benefits were similar despite the various numbers of training sessions applied. Further studies should add tactical behaviors as one of the outcomes for controlling the effects of SSG training programs.